Care to relieve pain-stress in preterm newborns - Di Gioia, C.; Bracceschi, R.; Copioli et al., C. (Acta Biomedica Atenei Parmensis, 2011)
Background and aim of the work: A variety of non-pharmacological pain-prevention and relief techniques have been studied to evaluate the pain reduction in neonates. The aim of our study was to compare the analgesic effect of sucking a pacifier with the use of eutectic mixture of local anaesthetics (EMLA) during venipuncture in preterm newborns, using physiological and behavioural parameters as indicators of pain. Methods: We analysed the reaction to invasive procedures in 17 preterm newborns. Our patients underwent repeated vein draws without pain relief, sucking a pacifier, after the application of EMLA; we also evaluated a group of patients approached for care without pricking. For each infant we recorded the average values of the physiological parameters at rest and after pain stimuli, behavioural conditions (crying or grimaces), number and time required for blood draw. Results: The maximum heart rate values, respiratory rate, and the maximum respiratory rate values presented a statistically difference only between subjects that underwent vein draws compared to subjects without pricking (p